The European Union and Korea between the US and China: Geopolitical aspects of connectivity from the soft to hard power approaches - Tereza Novotná (OrdnungsPolitisches Portal (OPO), 2021)
The paper examines the question how the EU and other countries who are in a similar position of "being caught between the US and China", such as South Korea, will shape their relationship with China and how their strategies complement, or contradict, the policies pursued by the US under the Trump and Biden Administrations. Even though Donald Trump has been more vocal in his bid to oppose China, the paper argues that there might be more continuity between Biden and Trump than Biden and Obama and the other Democratic predecessors. The second part of this paper investigates how the EU and South Korea interact with China's pre- and postCovid19 policies such as the Belt and Road Initiative (BRI). The paper explores how BRI has been countered by various forms of connectivity by Brussels and Seoul, how BRI fits within today's geopolitical landscape and whether and where there is any space for creating synergies between the EU and South Korea to offset it. Furthermore, the paper looks at other types of actions, such as the EU-China investment agreement (CAI) and human rights sanctions and how Beijing responded to these EU initiatives. The paper argues that a combination of softand hard-power approaches which Brussels have put forward towards Beijing may in the end work well for the EU as well as the US. The paper concludes by suggesting policy areas where cooperation rather than confrontation between all the actors is possible, such as health, trade, climate action and people-to-people exchanges.
Keywords: 330; EU foreign policy; connectivity; Korean peninsula; China; United States; Covid19